Case report: Gross total resection of a primary fourth ventricular meningioma using the telovelar approach in a dog - Jeong, Jaemin; Lee, Haebeom; Rho, Yoonho; Jeon, YoungJin (Frontiers in Veterinary Science, 2024)
An eleven-year-old spayed female Maltese dog presented with a two-month history of gait alterations, wide-based stance, and chronic vomiting. Neurological examination revealed cerebellovestibular signs, including head tilt, nystagmus, strabismus, intentional tremor, and hypermetric gait. MRI showed a mass with iso-to hypointensity on T1-weighted images and heterogeneous hyperintensity on T2-weighted images, with marked non-uniform contrast enhancement. The tumor was removed via a telovelar approach without intraoperative complications. Postoperatively, the dog developed non-ambulatory paraparesis with rigidity of the pelvic limbs but recovered ambulation within six days. Preoperative neurological signs progressively improved, and the patient was discharged without complications ten days after surgery. Histological examination revealed dense spindle cells with an abundant collagen matrix and oval-shaped nucleated cells with small whorls, leading to a diagnosis of transitional meningioma of the fourth ventricle. MRI followup at 8 months postoperative showed no definitive evidence of recurrence. At the final follow-up, 15.4 months postoperatively, mild neurological signs, including slight head tilt and subtle strabismus, remained but the rest of the neurological examination was normal. This is the first reported case of a meningioma in the fourth ventricle of a dog, successfully removed using the telovelar approach.